Design of restrained beams according to EC3 - Baptista, A. M. (1993)
This article presents an outline of the author's notes for the presentation of the EC3 specifications for the design of beams. In the first and second chapters a brief recall of the general basis of design and methods for structural analysis is given. The third chapter includes a recapitulation of the main rules to apply in the verification of ultimate states for beam cross-sections. Finally, in the fourth chapter, the most frequent serviceability limit states to take into account in the verification of beams are summarized.